Pengaruh Media Papan Bergerak terhadap Ketepatan Passing Atas Permainan Bola Voli - Salamanang, Riwalde; Hakim, Luqmanul (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to analyze the effect of overhead passing training using a moving board on the accuracy of overhead passing in volleyball among extracurricular students at SMA Hangtuah 1 Surabaya. The research method employed is an experimental method with a pretest-posttest design. The sample consisted of 15 volleyball extracurricular students from SMA Hangtuah 1 Surabaya, using a quantitative approach. The data collection instrument was an overhead passing accuracy test targeting a wall with boxes measuring 30 cm x 30 cm, conducted from a distance of 2–3 meters. Data were collected before and after the training intervention. The data analysis results showed that overhead passing training using a moving board significantly improved the accuracy of overhead passing against the boxed wall. This is evidenced by the t-test results, where the t-count value of 1.761 was greater than the t-table value of -9.176 (df = 14), and the significance value (2-tailed) was 0.000 < 0.05. Therefore, using a moving board as a training target positively impacts the improvement of overhead passing accuracy in volleyball.